Assessment of Posterior and Middle Facet Subluxation of the Subtalar Joint in Progressive Flatfoot Deformity. (October 2020) - de Cesar Netto, Cesar; Silva, Thiago; Li, Shuyuan; Mansur, Nacime Salomao; Auch, Elijah; Dibbern, Kevin; Femino, John E.; Baumfeld, Daniel
Background: Adult acquired flatfoot deformity (AAFD) is a complex 3-dimensional pathology characterized by peritalar subluxation (PTS) of the hindfoot. For many years, PTS was measured at the posterior facet of the subtalar joint. More recently, subluxation of the middle facet has been proposed as a more accurate and reliable marker of symptomatic AAFD, enabling earlier detection. The objective of this study was to compare the amount of subluxation between the medial and posterior facets in patients with AAFD. Methods: In this institutional review board-approved retrospective comparative study, a total of 76 patients with AAFD (87 feet) who underwent standing weightbearing computed tomography (WBCT) as a standard baseline assessment of their foot deformity were analyzed. Two blinded fellowship-trained orthopedic foot and ankle surgeons with >10 years of experience measured subtalar joint subluxation (as a percentage of joint uncoverage) at the both posterior and middle facets. One of the readers also measured the foot and ankle offset (FAO). PTS measurements were performed at the sagittal midpoint of the articular facets using coronal plane WBCT images. Intra- and interobserver agreement was measured for PTS measurements using the intraclass correlation coefficient (ICC). The intermethod agreement between the posterior and middle facet subluxation was assessed using Spearman's correlation and bivariate analysis. Paired comparison of the measurements was performed using the Wilcoxon test. A multivariate analysis and a partition prediction model were used to assess influence of PTS measurements on FAO values. P values of <.05 were considered significant. Results: ICCs for intra- and interobserver reliabilities were 0.97 and 0.93, respectively, for posterior and 0.99 and 0.97, respectively, for middle facet subluxation. The intermethod Spearman's correlation between subluxation of the posterior and middle facets was measured at 0.61. In a bivariate analysis, both measurements were found to be significantly and linearly correlated ( P < .0001; R 2 = 0.42). Measurements of middle facet subluxation were found to be significantly higher than those for posterior facet subluxation, with a median difference (using the Hodges-Lehman factor) of 17.7% ( P < .001; 95% CI, 10.9%-23.6%). We also found that for every 1% increase in posterior facet subluxation there was a corresponding 1.6-fold increase in middle facet subluxation. Only middle facet subluxation measurements were found to significantly influence FAO calculations ( P = .003). The partition prediction model demonstrated that a middle facet subluxation value of 43.8% represented an important threshold for increased FAO. Conclusion: This study is the first to compare WBCT measurements of subtalar joint subluxation at the posterior and middle facets as markers of PTS in patients with AAFD. We found a positive linear correlation between the measurements, with subluxation of the middle facet being significantly more pronounced than that of the posterior facet by an average of almost 18%. This suggests that middle facet subluxation may provide an earlier and more pronounced marker of progressive PTS in patients with AAFD. Level of Evidence: Level III, retrospective comparative cohort study.